Generalized Methods on Access Bank Share Price Changes and Variations in Nigeria Stock Market - CHIGOZIE, Okere; ELE, Chims Benjamin; UCHENNA, Amadi Innocent (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose: Stock market performance and operation have been widely recognized as a viable investment field in financial markets. This paper studied the share price movement of Access Bank, PLC.Methodology:The share price data was subjected to a 3-step transition matrix for independent share prices, which enabled us to proffer precise conditions for obtaining future share price changes and placed criteria that enabled us to come up with a 2x2 matrix solution of Principal Component Analysis (PCA) on the share price of Access bank.Findings: The solution matrix of the stochastic analysis showed that Access Bank PLC has the best probability of price increasing shortly by 12%, the best probability of reducing in the future by 21%, and the best probability of no change shortly by 20%.Implication:More so, an increase in the trading days also increases the value of future share price changes, and other statistical variables were also found. Finally, the influences of the relevant parameters of stock market variables were effectively discussed in this paper.